Managing misbehaviour in schools - Charlton, Tony; David, Kenneth (Routledge, 1993)
A wide-ranging survey of both the theoretical and practical understanding of children's behaviour in schools. It provides ideas and suggestions on the management of behaviour problems in everyday classroom life.